2010
DOI: 10.1186/1472-6831-10-24
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of determinants for high and low dental caries prevalence in Nevada youth

Abstract: BackgroundThe main purpose of this study was to compare the 30% of Nevada Youth who presented with the highest Decayed Missing and Filled Teeth (DMFT) index to a cohort who were caries free and to national NHANES data. Secondly, to explore the factors associated with higher caries prevalence in those with the highest DMFT scores compared to the caries-free group.MethodsOver 4000 adolescents between ages 12 and 19 (Case Group: N = 2124; Control Group: N = 2045) received oral health screenings conducted in publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 13 publications
4
48
1
5
Order By: Relevance
“…Dental caries remains a major public health problem due to its widespread nature, high cost of treatment, and it is a main cause of oral pain and tooth loss which ultimately affects quality of life [1,2]. Current evidences show that dental caries is a multifactorial disease and complexly modulated by genetic, behavioral, social and environmental factors [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries remains a major public health problem due to its widespread nature, high cost of treatment, and it is a main cause of oral pain and tooth loss which ultimately affects quality of life [1,2]. Current evidences show that dental caries is a multifactorial disease and complexly modulated by genetic, behavioral, social and environmental factors [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidences show that dental caries is a multifactorial disease and complexly modulated by genetic, behavioral, social and environmental factors [2,3]. Considering this complex etiology of dental caries the major challenge for oral epidemiologists is to identify potential determinants and predictors of dental caries in order to target socially appropriate public health measures to control the disease and its unpleasant consequences [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified associations between numerous factors and dental caries, supporting the agreement that dental caries is a multifactorial disease modulated by genetics, behaviour and environment (15). It is well known that caries depends on several factors comprising the interaction of agent, host, environment and time.…”
Section: Introductionmentioning
confidence: 81%
“…The following variable were included in the analyses as potential confounders: family socioeconomic status at baseline [17], age, gender, second-hand tobacco smoke exposure from birth to the age of 3 years [18], and preterm birth (before the week 37) [19]. Information on these covariates was obtained from the baseline questionnaire and later follow-up surveys.…”
Section: Methodsmentioning
confidence: 99%